Pengaruh Customer Relationship Marketing Dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan: (Studi pada Klinik Kecantikan dr. Amalia Di Sumedang) - Latief Z. Nur (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
This research was conducted on beauty clinic customers dr. Amalia has bought skin care and facial treatment more than three times. The goal is to identify: customer relationship marketing and service quality on customer loyalty and how much influence the customer relationship marketing of customer loyalty and the influence of service quality on customer loyalty. Population in this research are customers who have registered at the beauty clinic dr. Amalia Sumedang. While the samples used in this study were 200 customers. Analysis data in this study using descriptive analysis and verification analysis. Testing of research instruments conducted using validity and reliability testing. For data analysis using classical assumption testing, multiple linear regression analysis and coefficient of determination analysis, which previously performed data transformation first. As for the hypothesis test using the t test for partial testing. The result of descriptive analysis of customer relationship marketing is in very good category, service quality is in very good category and customer loyalty is in high category. Based on the partial test results of customer relationship marketing have a positive and significant influence customer loyalty, so does the quality of service have a positive and significantly influence customer loyalty.